Genetic suspects: global governance of forensic DNA profiling and databasing - Hindmarsh, Richard; Prainsack, Barbara (Cambridge University Press, 2010)
"The introduction of DNA profiling and databasing into the criminal justice system, which began in 1988, when English baker Colin Pitchfork was the first person convicted through the use of DNA evidence (Sanders 2000C001-001)"--